Epitope mapping of the White Spot Syndrome Virus (WSSV) VP28 monoclonal antibody through combined in silico and in vitro analysis reveals the potential antibody binding site. (April 2020) - Shine, P.V.; Shankar, K.M.; Abhiman, B.; Sudheer, N.S.; Patil, R.
Abstract: White Spot Syndrome Virus (WSSV) infecting shrimp is an enveloped double-stranded DNA virus. The WSSV is a member of the genus Whispovirus . The envelope protein VP28 is the most investigated protein of WSSV. In the present study, the epitope mapping of the monoclonal antibody (MAb) C-33 was carried out. Based on the epitope mapping results, an antigen-antibody interaction model was derived. Peptide scanning and confirmation of epitopes of MAb C-33 were carried out using the sequence data. The MAb was reactive to the epitope of both recombinant VP28 and the whole virus. The results of the study indicated the presence of an epitope region. The epitope region is found positioned within two peptides, covering 13 amino acids. Framework and CDR (complementarity determining regions) of heavy and light chain (VH & VL) sequences showed identity to germline immunoglobulin sequences. The Web Antibody Modelling (WAM) selected for further evaluation based on a comparative analysis of WAM and Rosetta server-generated models of the Fv region. The docking study using WAM generated model revealed that the residues from LEU98 to GLY105 are active in antibody binding. The findings of this study could form a structural basis for further research in VP28 based diagnostics and therapeutics or vaccine discovery. Highlights: The protective epitope of the WSSV VP28 is mapped through peptide scanning using a monoclonal antibody. A linearepitope region within two peptides, in a boundary of 13 amino acids was detected. Framework and CDR regions of VH and VL sequences showed identities to germline Immunoglobulin sequences. A comparative analysis of WAM and Rosetta server-generated models of the Fv region was carried out. Docking study revealed that the residues from LEU 98 to GLY105 are active in antibody binding.